EFFECTIVENESS OF HANDS-ON ACTIVITY AND MINDS ON ACTIVITY BASED ON CONTEXTUAL APPROACH TOWARD MATHEMATICS LEARNING OUTCOMES - Annisa Mutiara Sukma; Aris Thobirin (Universitas Ahmad Dahlan, 2019)
Until now, in general, mathematics is still a subject with learning outcomes that tend to be unsatisfactory, including data shown by observations of mathematics learning outcomes at Islamic Junior High School (MTs) Wahid Hasyim Yogyakarta. It can be seen from the few students who are active in asking questions when finding difficulties and students who want to go forward to work on the problem. This study aims to determine contextual learning effectiveness through Hands-on Activity and Minds on Activity in improving student learning outcomes. This study's population were all eighth-grade students of MTs Wahid Hasyim Sleman Regency 2015/2016 Academic Year consisting of 3 classes. The class sampling technique is that classes are taken randomly from classes in the population, and each class is homogeneous. The class drew results. It was found that class VIII A was the experimental class and class VIII C was the control. Data collection is done using the test method. The instrument test uses content validity. Data analysis techniques used for analysis prerequisite tests include normality test, homogeneity test, and hypothesis testing. After researching with Randomized Posttest-Only Comparison Group Design with a population of VIII class of MTs Wahid Hasyim, the data showed that 1) t-test results obtained tcount = 2.0217> ttable = 2.0190, this means that there are differences in learning outcomes student mathematics between students who learn using contextual learning models with students who learn using conventional learning models. 2) the t-test was obtained tcount = 2.0217> ttable = 1.6826, this shows that Hands-On Activity and Minds On Activity in mathematics learning with contextual approaches are more effective than mathematics learning using conventional learning models of students' mathematics learning outcomes 7th MTs Wahid Hasyim SlemanÂ Academic Year 2015/2016.